การพัฒนาระบบสารสนเทศเพื่อการประกันคุณภาพหลักสูตรตามกรอบมาตรฐาน The Development of Information System for Curriculum Quality Assurance under the Qualifications Framework for Higher Education - พระฉาย แสงเพ็ชร; อารีราษฎร์ ธรัช; อารีราษฎร์ วรปภา; คูกนก สุขแสง (Science Essence Journal, 2014)
การวิจัยนี้มีวัตถุประสงค์เพื่อพัฒนาระบบสารสนเทศเพื่อการประกันคุณภาพหลักสูตรตามกรอบมาตรฐานคุณวุฒิระดับอุดมศึกษา การวิจัยแบ่งขั้นตอนออกเป็น 4 ระยะ คือ 1) การศึกษาแนวทางการออกแบบระบบสารสนเทศ 2) การศึกษาคุณภาพผลการออกแบบระบบสารสนเทศ 3) การศึกษาคุณภาพผลการพัฒนาระบบสารสนเทศ และ 4) การทดลองใช้ระบบสารสนเทศ กลุ่มตัวอย่างที่ศึกษาเป็นคณาจารย์จำนวน 20 คน สังกัดใน 5 หลักสูตรที่ปรับปรุงตามกรอบมาตรฐานคุณวุฒิระดับอุดมศึกษา เครื่องมือวิจัยประกอบด้วย 1) แบบสอบถามคุณภาพผลการออกแบบระบบ 2) แบบสอบถามคุณภาพผลการพัฒนาระบบ 3) ระบบสารสนเทศเพื่อการประกันคุณภาพหลักสูตรตามกรอบมาตรฐานคุณวุฒิระดับอุดมศึกษา และ 4) แบบสอบถามผลการทดลองใช้ระบบ สถิติที่ใช้ในการวิจัยเป็นสถิติขั้นพื้นฐาน ได้แก่ ดัชนีวัดความสอดคล้อง ค่าเฉลี่ย และค่าเบี่ยงเบนมาตรฐาน ผลการวิจัยพบว่า ระยะที่ 1 แนวทางการออกแบบระบบสารสนเทศเพื่อการประกันคุณภาพหลักสูตรตามกรอบมาตรฐานคุณวุฒิระดับอุดมศึกษาพบว่า ระบบสารสนเทศควรแบ่งการปฏิบัติงานออกเป็น 9 โมดูลที่มีลักษณะ บทบาทหน้าที่ และความสัมพันธ์ขององค์ประกอบในการรับส่งสารสนเทศที่แตกต่างกัน ประกอบด้วย 1) โมดูลสิทธิ์ผู้ใช้งาน 2) โมดูลการสื่อสาร 3) โมดูลผู้สอน 4) โมดูลผู้เรียน 5) โมดูลผู้ประกอบการหรือพี่เลี้ยง 6) โมดูลรายละเอียดหลักสูตร 7) โมดูลรายละเอียดและผลการดำเนินการของรายวิชา 8) โมดูลรายละเอียดและผลการดำเนินการของการฝึกประสบการณ์ภาคสนาม และ 9) โมดูลผลการดำเนินการหลักสูตร ระยะที่ 2 ความคิดเห็นของผู้เชี่ยวชาญที่มีต่อคุณภาพการออกแบบระบบ การวิจัยพบว่าภาพรวมของการออกแบบระบบมีความเหมาะสมอยู่ในระดับมากที่สุด ( = 4.77, S.D. = 0.44 ) ทั้งในด้านการกำหนดลักษณะ บทบาทหน้าที่ และความสัมพันธ์ขององค์ประกอบต่าง ๆ ระยะที่ 3 ความคิดเห็นของผู้เชี่ยวชาญที่มีต่อคุณภาพการพัฒนาระบบ การวิจัยพบว่าภาพรวมของการพัฒนาระบบมีความเหมาะสมอยู่ในระดับมากที่สุด ( = 4.65, S.D. = 0.49 ) ทั้งในด้านการตอบสนองต่อความต้องการ ความถูกต้องของฟังก์ชัน ผลลัพธ์น่าเชื่อถือ มีความสะดวก และมีความปลอดภัย ระยะที่ 4 ความคิดเห็นของคณาจารย์ที่มีต่อการทดลองใช้ระบบ การวิจัยพบว่าภาพรวมของการพัฒนาระบบมีความเหมาะสมอยู่ในระดับมากที่สุด ( = 4.67, S.D. = 0.48 ) ทั้งในด้านการตอบสนองต่อความต้องการของผู้ใช้ ความถูกต้องของฟังก์ชัน ผลลัพธ์น่าเชื่อถือ มีความสะดวก และมีความปลอดภัย The purposes of this research was to develop an Information System for Curriculum Quality Assurance under the Qualifications Framework for Higher Education. The research was divided into 4 stages including: 1) Conducting a study on guidelines for information system design; 2) Conducting a study on quality of information system design; 3) Conducting a study on quality of information system development; and 4) Conducting a trial on information system usage. Sample group used in this study were 20 lecturers who were under 5 curriculums improved by the Qualifications Framework for Higher Education. Research tools used in this research were: 1) questionnaire on information system design; 2) questionnaire on quality of information system development; 3) Information system for Curriculum Quality Assurance under the Qualifications Framework for Higher Education; and 4) questionnaire on result of information system usage. The statistics used in this research were basic statistics including index of item objective congruence, average and the standard deviation. The research findings were as follows: In stage 1 conducting the study on guidelines for information system design for Curriculum Quality Assurance under the Qualifications Framework for Higher Education. This research was found that operation of information system should be divided into 9 modules with different characteristics, roles and functions, and relationship of the components for distribution of information including: 1) Authentication Module; 2) Communication Module; 3) Teacher Module; 4) Student Module; 5) Businessman Module; 6) Program Specification Module; 7) Course Specification Module; 8) Experience Specification Module; and 9) Learning Outcome Module. In stage 2 experts’ opinions on quality of information system design. This research was found that overall design of information system was in the highest level of appropriateness ( = 4.77, S.D. = 0.44 ) on characteristic specifications, roles and functions, and relationships of the components for distribution of information. In stage 3 experts’ opinions on quality of information system development. This research was found that overall development of information system was in the highest level of appropriateness ( = 4.65, S.D. = 0.49 ) on relevant and precision, function’s accuracy and complete, result’s reliable, accessible, and secure or safety. In stage 4 the lecturers’ opinions on the trials of information system usage. This research was found that overall development of information system was in the highest level of appropriateness ( = 4.67, S.D. = 0.48 ) on relevant and precision with users, function’s accuracy and complete, result’s reliable, accessible, and secure or safety.